Using participatory methods to develop a narrative intervention to alleviate distress in children hospitalised with TB in South Africa: The DIMPle project - Caitlin D. October; Dzunisani P. Baloyi; Lario Viljoen; Rene Raad; Dillon T. Wademan; Megan Palmer; Juli Switala; Michaile G. Anthony; Karen Du Preez; Petra De Koker; Anneke C. Hesseling; Bronwyne Coetzee; et al. (PLoS ONE, 2025)
Children who are hospitalised for tuberculosis (TB) experience challenges that put them at risk of developing emotional, behavioural, and social difficulties. In this methodological paper, we showcase the development of a narrative intervention toolkit with key components of the resulting version 1.0 tool. The study design was participatory and pragmatic, with researchers working with the routine staff of TB hospital wards, children admitted and their caregivers, to iteratively understand and improve children’s experiences of hospitalisation. The project included three phases: (1) a situational analysis to map children and healthcare providers’ perspectives on priorities and potential intervention components, (2) co-development of a beta-version of the intervention, and (3) piloting and incremental refinement toward a version 1.0 of the intervention. The intervention toolkit combined a series of activities alongside the story of ‘Courageous Curly’ to facilitate children’s engagement with their own experiences of hospitalisation, including psychosocial and treatment challenges, captured, and described throughout data collection. We found that dividing the story into short chapters facilitated children’s engagement with the section of story that is being told on a specific day. Each chapter of the story follows/mimics a different stage children can expect during their treatment journey while hospitalised for TB care. Implementation and evaluation of such interventions can mitigate the psychosocial impact of TB in children and inform policies to improve their overall TB care.